Computer analysis of images and patterns. 17th International Conference, CAIP 2017, Ystad, Sweden, August 22-24, 2017, Proceedings /: 17th International Conference, CAIP 2017, Ystad, Sweden, August 22-24, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available